Assessment of factors influencing on the success of public-private partnerships infrastructure projects in Vietnam - Nguyen Quoc Toan; Dinh Tuan Hai (Archives of Civil Engineering, 2023)
The implementation of public-private partnerships has become one of the effective models of cooperation between the public and private sectors in the development of infrastructure in Vietnam. This model has been adopted in Vietnam for many years and is intended to help governments build infrastructure and provide an opportunity to reduce government debt profiles. This study aims to identify the most critical factors that could determine the success of these projects. A questionnaire was conducted based on the participants’ experience in the implementation of public-private partnerships projects and a total of 216 respondents were received. A regression analysis shows that six critical success factors, including factors relevant to public sector, factors relevant to private sector, factors relevant to selected process partnerships, factors relevant to risk management systems, factors relevant to project information, and factors relevant to natural environment. The findings indicated that the most effective development projects could be carried out via PPPs if the government could focus on these important factors in the implementation process. The results will influence political development towards PPP and guide partners in developing public-private partnerships projects.